2018
DOI: 10.1002/ange.201809889
|View full text |Cite
|
Sign up to set email alerts
|

Nickel as a Lewis Base in a T‐Shaped Nickel(0) Germylene Complex Incorporating a Flexible Bis(NHC) Ligand

Abstract: Flexible, chelating bis(NHC) ligand 2, able to accommodate both cis-and trans-coordination modes, was used to synthesize (2)Ni(η 2 -cod), 3. In reaction with GeCl2, this produced (2)NiGeCl2, 4, featuring a T-shaped Ni(0) and a pyramidal Ge center. Complex 4 could also be prepared from [(2)GeCl]Cl, 5, and Ni(cod)2, in a reaction that formally involved Ni-Ge transmetalation, followed by coordination of the extruded GeCl2 moiety to Ni. A computational analysis showed that 4 possesses considerable multiconfigurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 82 publications
(16 reference statements)
2
19
0
Order By: Relevance
“…Reduced conformational fluxionality in complexes containing bis-(NHC)Ni fragments was shown to lead to broad, poorly resolved resonances in the solution NMR spectra, as well as lowering of the expected time-averaged symmetry. [27] An Xray diffraction experiment on 2 confirmed chelation of the ligand to Ni in a bent geometry (C1-Ni1-C8 107.9(1)8) (Figure S28) and the h 2 -coordination of 1,5-cyclooctadiene.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Reduced conformational fluxionality in complexes containing bis-(NHC)Ni fragments was shown to lead to broad, poorly resolved resonances in the solution NMR spectra, as well as lowering of the expected time-averaged symmetry. [27] An Xray diffraction experiment on 2 confirmed chelation of the ligand to Ni in a bent geometry (C1-Ni1-C8 107.9(1)8) (Figure S28) and the h 2 -coordination of 1,5-cyclooctadiene.…”
mentioning
confidence: 92%
“…[26] We reported on a bis(NHC) 2 Ni 0 -GeCl 2 complex incorporating a siloxane-linked (NHC) 2 Ni 0 fragment with a bent L 2 M geometry. [27] Computational studies indicated that this fragment featured the frontier orbitals necessary for efficient h 2interactions with p-acidic ligands. [18c, 28] Thus, we hypothesized that a bis(NHC) 2 supported Ni 0 would be an excellent candidate for stabilizing side-on, h 2 -N 2 O complexes, especially taking into account the resilience of NHC ligands to oxidation.…”
mentioning
confidence: 99%
“…The Ni 0 site presents a planar and T-shaped geometry (Σ°N i = 359.91) with a large PÀ NiÀ C1 NHC angle (164.51°), in contrast to the case of silylene-Ni(NHC) 2 complex XII with a trigonal planar Ni site (C NHC À NiÀ C NHC = 111.4°). [11] A similar geometry was observed for other M 0 !metallylene complexes IX-X (M=Ni, Pt) [8,9] as well as for L 2 Ni!Lewis acid complexes. [16] To gain more insight into the electronic structure of Ni 0 !silylene complex 4, DFT calculations have been performed at the M06/Def2TZVP//M06/6-31G(d) level of theory (Figure 4).…”
mentioning
confidence: 99%
“…Therefore, heavier divalent species (E=Ge, Sn, Pb) present stronger tendency to form M!ER 2 complexes V. Indeed, to date, the only known compounds of this type V are germylene-, stannylene-and plumbylene-based complexes (VII-X). [6][7][8][9] DFT calculations predicted that, although germylenes and stannylenes are able to form complexes of type V, lighter analogues (silylenes and carbenes) tend to form classical R 2 ED!M complexes IV, [7] although several methanediide-TM complex, featuring a pyramidalized carbon centre, have been described. [10] To the best of our knowledge, complexes V involving a silylene fragment M!…”
mentioning
confidence: 99%
“…[1][2][3] In this regard, heavier tetrylenes (:ER2; E = Si, Ge, Sn, Pb) offer unique opportunities as single-site ambiphiles (σ-donating lone pair and empty p orbital), revealing unusual coordination modes and reactivity. [4][5][6][7][8][9][10][11][12] Moreover, they represent the prospects of new avenues for transition metal/P-element cooperation. [13][14][15][16][17][18][19][20][21][22][23][24][25] However, the coordination chemistry of tetrylenes remains considerably less explored than their lighter carbene congeners, in no little part due to reduced stability.…”
mentioning
confidence: 99%